2009
DOI: 10.4315/0362-028x-72.7.1481
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bacteriophages in Reducing Escherichia coli O157:H7 on Fresh-Cut Cantaloupes and Lettuce

Abstract: Consumption of produce contaminated with Escherichia coli O157:H7 has resulted in cases of foodborne illness. We determined the efficacy of a mixture of three E. coli O157:H7-specific bacteriophages (ECP-100) in reducing the number of viable E. coli O157:H7 on contaminated fresh-cut iceberg lettuce and cantaloupe. E. coli O157:H7 was spot inoculated on lettuce pieces (9 cm2) with a population of 3.76 log CFU/cm2, allowed to dry, and then sprayed with a control (phosphate-buffered saline) or ECP-100 to deliver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
94
2
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(115 citation statements)
references
References 26 publications
10
94
2
9
Order By: Relevance
“…Phages were not inactivated before enumeration; previous studies have shown that there are no significant differences among results with and without phage inactivation. 26,27 Statistical analysis…”
Section: Salmonella Challenges On Turkeymentioning
confidence: 99%
“…Phages were not inactivated before enumeration; previous studies have shown that there are no significant differences among results with and without phage inactivation. 26,27 Statistical analysis…”
Section: Salmonella Challenges On Turkeymentioning
confidence: 99%
“…In addition, treatment of vegetables, such as cantaloupe and lettuce, with a phage cocktail to control E. coli O157:H7 showed a significant reduction in the bacteria (64). Although broad-host-range phages infecting several different genera of bacteria were previously reported (6,31,34) and many phages have been developed and evaluated for control of food-borne Salmonella and E. coli O157:H7, bacteriophages that simultaneously control these two pathogens have been rarely reported (24).…”
mentioning
confidence: 99%
“…Carvalho et al (2010) administered campylobacter phage to poultry by oral gavage Spraying of phage cocktail on spinach blades resulted in a 4.5 log reduction of CFU after 2 h of phage addition Patel et al 2011 No survivors detectable on spinach and lettuce leaves after 10 min. of phage addition combined with cinnamaldehyde treatment Viazis et al 2011 Significant reduction in CFU on lettuce and cantaloupe after 2 days of spraying with phage cocktail (ECP-100) Sharma et al 2009 Phage cocktail e11/2, e4/1c, pp01 applied on meat surface resulted in eradication of E.coli in seven of nine samples…”
Section: Phage Therapymentioning
confidence: 99%